Mummies in the Morning - Osborne, Mary Pope (New York Random House, 1993)
Jack and his younger sister take a trip in their tree house back to ancient Egypt, where they help a queen's mummy continue her voyage to the Next Life.
Include Colour Illustration
Keywords: Mummies -- Magic -- Tree houses